Idiopathic polyhydramnios: persistence across gestation and impact on pregnancy outcomes. (April 2016) - Odibo, Imelda N.; Newville, Trista M.; Ounpraseuth, Songthip T.; Dixon, Mandi; Lutgendorf, Monica A.; Foglia, Lisa M.; Magann, Everett F.
Abstract: Purpose: To investigate the likelihood of resolution of idiopathic polyhydramnios in pregnant women and compare outcomes between resolved and persistent cases. Methods: One hundred and sixty-three women with idiopathic polyhydramnios who delivered at two medical centers during a 3 year period (January 2012–January 2015) were included in the study. Exclusion criteria included congenital fetal anomalies, maternal diabetes, isoimmunization, fetal infection, placental tumors or anomalies, and multiple gestation. Polyhydramnios was defined as SDP ≥ 8 cm or AFI ≥ 24 cm. Resolved cases were defined as those with AFI and/or SDP falling and remaining below 24 cm and 8 cm respectively. Pregnancy outcomes were compared between resolved and persistent cases. Two-sample t -test or Wilcoxon rank-sum test was used for continuous variables while chi-square test or Fisher's exact test was used for categorical measures. Results: Resolution was noted in 61 of 163 (37%) patients. There were no differences in maternal age, gravidity or parity between resolved and persistent cases. Mean gestational age at diagnosis of polyhydramnios and overall mean AFI were significantly lower in the cases that resolved (29.7 ± 4.5 weeks vs 33.4 ± 4.1 weeks, p < 0.0001; 23.3 ± 3.5 cm vs 25.8 23.3 ± 4.0 cm, p = 0.0002). Similar to AFI measurements, mean SDP was also lower in cases with resolution ( p = 0.002). There was no difference in induction rates, mode of delivery, amnioinfusion rates, meconium staining of amniotic fluid and fetal heart rate abnormalities influencing intrapartum management between the two groups. Induction of labor for fetal indication and rupture of membranes were significantly more common in the persistent group. Cesarean delivery for abnormal lie and fetal distress did not differ between the groups. There was an increased risk of macrosomia (>4000 g) and preterm delivery (<37 weeks) in the persistent group ( p < 0.05). Conclusions: Resolution rate was approximately 37% and more likely in cases diagnosed earlier in pregnancy and with lower mean amniotic fluid volume. Preterm delivery and macrosomia were more common in cases that persisted across gestation.